Efeitos da exposição subsequente a estresses abióticos na termotolerância e sobrevivência em condições gastrointestinais simuladas de salmonella enteritidis pt4 e salmonella typhimurium pt4 - Melo, Adma Nadja Ferreira de (2016)
Salmonella enterica subespecie enterica is a pathogen frequently involved in outbreaks worldwide. Serovars S. Enteritidis e S. Typhimurium belonging to paghe type 4 (PT4) are prevalent among the etiological agentes of salmonellosis outbreaks involving chicken meat. The aim of this study was to assess changes in thermotolerance and capability to survive to gastrointestinal conditions of Salmonella Enteritidis PT4 and S. Typhimurium PT4 incorporated in chicken breast following exposure to abiotic stresses (cold, acid and osmotic) imposed during food processing. The effects of stressing conditions imposed by Origanum vulgare L. essential oil (oregano), a candidate substance for use as antimicrobial in foods, was also assessed. The exposure to cold stress (5°C for 5 h) did not result in increased tolerance to acid stress (lactic acid at 5 μL/g and 2.5 μL/g) in all tested strains. Cells of S. Typhimurium and S. Enteritidis previously exposed to acid stress showed higher tolerance to osmotic stress (NaCl at 75 mg/g or 37.5 mg/g,) compared to non-acid-exposed cells. The exposure to osmotic stress without previous exposure to acid stress caused a salt-concentration dependent decrease in S. Enteritidis or S. Typhimurium. Exposure to oregano essential oil at subinhibitory concentrations (1.25 μL/g and 0.625 μL/g) decreased the acid and omostic tolerance in both S. Enteritidis and S. Typhimurium. The subsequent exposure to cold, acid and osmotic stress conditions increased the thermotolerance in all test strains. Under simulated gastrointestinal conditions, the cells that survived the subsequent stress exposure (persisters) showed higher tolerance to acidic conditions (approximately 1.2 log CFU/g) compared with control cells. Persisters cells of S. Enteritidis and S. Typhimurium showed higher survival rates at the end of the in vitro digestion. These results show that subsequent exposure to stress conditions increase the thermotolerance and enhanced the survival under gastrointestinal condition in S. Enteritidis PT4 and S. Typhimurium PT4, which may contribute to the persistence of this pathogen within food matrix and host.